An Improved Method of Documenting Activity Patterns of Post-Emergence Polar Bears (Ursus maritimus) in Northern Alaska - Smith, Tom S.; Miller, Julie A.; Layton, Cali (ARCTIC, 2013)
Throughout their circumpolar range, pregnant female polar bears (Ursus maritimus) create snow dens in which they give birth to altricial cubs. Because polar bear neonates are born in such an undeveloped state, their survival requires a long, undisturbed period of in-den development. To mitigate human impacts on denning bears, it is necessary to understand the chronology of denning, the behaviors of denning bears, and their sensitivity to human activities. Since 2002, we have studied the den emergence behaviors of polar bears in northern Alaska; however, we moved from using on-site observers (2002 – 03) to using autonomous video systems (2005 – 08). Here we compare the duration, activity budgets, and behaviors of polar bears to see whether observation methods affected their activities. Camera systems recorded nearly 10 times the data per den recorded by human observers (526 h/den and 57 h/den respectively). We found no difference between the two study periods in emergence dates, duration at den sites, abandonment dates, or activity budgets for polar bears. We observed a 16-fold reduction in the number of bear-human interactions when using cameras instead of human observers. There was, however, a marked increase in the intensity of response when using cameras (125 m) as compared to observers in blinds (400 m). An understanding of these activity patterns can be used to manage human activities near dens so as to minimize disturbance. À l’échelle de leur aire de répartition circumpolaire, les ourses polaires (Ursus maritimus) en gestation se créent une tanière de neige pour donner naissance à leurs oursons à développement tardif. Puisque les nouveau-nés de l’ourse polaire naissent dans un état si peu développé, leur survie nécessite une longue période de développement non perturbé en tanière. Afin d’atténuer les incidences de l’être humain sur les ours en tanière, il est nécessaire de comprendre la chronologie de la mise bas, les comportements des ours en tanière et leur sensibilité à l’activité humaine. À partir ...